Antimicrobial photodynamic therapy for severe acute radiodermatitis in patients undergoing head and neck radiotherapy: a case series - Costa e Silva, Isabella Macedo; Custódio, Carolina de Souza; Monteiro, Mylene Martins; Freitas, Karina Alexandra Batista da Silva; Lima, Talita Oliveira de; Abreu, Wenzel Castro de; Reis, Ricardo Gomes dos; Guerra, Eliete Neves Silva; Ferreira, Elaine Barros; Reis, Paula Elaine Diniz dos (Frontiers in Oncology, 2026)
IntroductionAcute radiodermatitis (ARD) is a frequent and debilitating inflammatory toxicity in patients undergoing head and neck radiotherapy (RT). In severe cases, ARD may progress to moist desquamation, with the potential for ulceration. Colonization or infection with Staphylococcus aureus is a critical independent risk factor for worsening ARD. Antimicrobial photodynamic therapy (aPDT) has emerged as a promising adjunctive therapeutic approach, with potential to reduce microbial burden, modulate inflammation, and accelerate tissue repair. This study aimed to evaluate the clinical effects of aPDT in patients with severe ARD.MethodsWe conducted a case series, according to the CARE Statement Guideline, over an eight-month period involving five patients with severe ARD (GRA-L scale ≥ 5) who received aPDT following a standardized protocol. The protocol involved the topical application of methylene blue 1% as the photosensitizer followed by irradiation with a 660-nm diode laser delivering an energy density of 91.836 J/cm2 per point, with sessions repeated every 72 hours. Clinical assessments performed at the same interval and included photographic documentation and severity scoring with the GRA-L scale.ResultsaPDT led to significant clinical improvement in all five cases. ARD severity decreased from a mean initial grade of 6 (range: 5–8) to grade 1 in all patients, with no progression to more advanced grades after therapy initiation. Clinical stability was maintained until completion of the prescribed RT course, including the case in which aPDT was initiated during treatment. In the post-RT cases, recovery occurred within 6 to 15 days after aPDT initiation. No adverse effects related to aPDT were observed.ConclusionsThis case series provides preliminary evidence that aPDT may assist in the management of severe ARD in patients undergoing head and neck RT. While the observed improvements were encouraging, these findings are exploratory and require confirmation in larger, controlled studies before aPDT can be considered within standardized supportive care approaches.